The Effectiveness Of Reflective Enrichment Program (Rep) In Enhancing Reflective Thinking And Metacognitive Skills Of Jordanian Gifted And Talented Students (Gts) - Abusaif, Radwan Abdalsalam Radwan (2021)
The Reflective Enrichment Program (REP), an entirely new enrichment program, was developed and tested in this study to fill in the research gaps on intervention that train higher order thinking skills among gifted and talented students (GTS) in Jordan. REP was designed specifically to enhance GTS’ reflective thinking and metacognitive skills. This study has six research objectives that tested the effectiveness of REP in enhancing GTS’ overall reflective thinking and metacognitive skills, as well as its dimensions. A Pre-test Post-test Control Group Design was carried out in this experimental study. The research design included an experimental group (n=32) and a control group (n=32). The experimental group has undergone 24 sessions of REP program while the control group experienced the traditional enrichment activities. Reflective thinking among GTS was measured by the Reflective Thinking Questionnaire (RTQ), while their metacognitive skills were gauged by the Metacognitive Skills Questionnaire (MSQ). Both descriptive and inferential analyses were carried out. The results of Analysis of Covariance (ANCOVA) showed that five out of six null hypotheses tested were rejected. The results demonstrated that REP has positive effects on GTS’s overall reflective thinking [F (2.37) = 32.56, p (0.00) < 0.05)] as well as in its knowledge [F (2.38) = 9.57, p (0.00) < 0.05)] and application dimensions [F (2.36) = 44.32, p (0.00) < 0.05)]. As for metacognitive skills, REP has significantly improved overall metacognitive skills [F (2.28) = 11.76, p (0.00) < 0.05] and metacognitive knowledge [F (2.32) = 12.44, p (0.00) < 0.05)].